Emerging SARS‐CoV‐2 variants can potentially break set epidemiological barriers in COVID‐19. Issue 4 (29th November 2021) - Kumar, Ashutosh; Parashar, Rakesh; Kumar, Sujeet; Faiq, Muneeb A; Kumari, Chiman; Kulandhasamy, Maheswari; Narayan, Ravi K.; Jha, Rakesh K.; Singh, Himanshu N.; Prasoon, Pranav; Pandey, Sada N.; Kant, Kamla
Abstract: Young age, female sex, absence of comorbidities, and prior infection or vaccination are known epidemiological barriers for contracting the new infection and/or increased disease severity. Demographic trends from the recent coronavirus disease 2019 waves, which are believed to be driven by newer severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) variants, indicate that the aforementioned epidemiological barriers are being breached and a larger number of younger and healthy individuals are developing severe disease. The new SARS‐CoV‐2 variants have key mutations that can induce significant changes in the virus‐host interactions. Recent studies report that, some of these mutations, singly or in a group, enhance key mechanisms, such as binding of the receptor‐binding domain (RBD) of the viral spike protein with the angiotensin‐converting enzyme 2 (ACE2) receptor in the host‐cells, increase the glycosylation of spike protein at the antigenic sites, and enhance the proteolytic cleavage of the spike protein, thus leading to improved host‐cell entry and the replication of the virus. The putative changes in the virus–host interactions imparted by the mutations in the RBD sequence can potentially be the reason behind the breach of the observed epidemiological barriers. Susceptibility for contracting SARS‐CoV‐2 infection and the disease outcomes are known to be influenced by host‐cell expressions of ACE2 and other proteases. The new variants can act more efficiently, and even with the lesser availability of the viral entry‐receptor and the associated proteases, can have more efficient host‐cell entry and greater replication resulting in high viral loads and prolonged viral shedding, widespread tissue‐injury, and severe inflammation leading to increased transmissibility and lethality. Furthermore, the accumulating evidence shows that multiple new variants have reduced neutralization by both, natural and vaccine‐acquired antibodies, indicating that repeated and vaccine breakthrough infections may arise as serious health concerns in the ongoing pandemic. Highlights: Emerging SARS‐CoV‐2 variants: Harbor key mutations altering the virus‐host interactions. Show more efficient host‐cell entry and greater replication resulting in higher viral loads, prolonged viral shedding, and greater tissue injury. Show reduced neutralization by natural and vaccine acquired antibodies. Causing symptomatic illness in increasing number of young, women, and healthy individuals.